A Comparative Antimicrobial Analysis of Commercially Available Toothpaste; An In-Vitro Study - Memuna Satti; Dr Farwa Rais; Dr Zainab Qasim; Dr Zuleikha Malik; Dr. Maryam Maqsood; Dr. Kunza Naveed Asdaq (ziauddin University, 2024)
Background: The incorporation of certain antimicrobial materials is an effective way to prevent early carious lesions. The additive effect of improving hygiene habits and using antimicrobial toothpaste for brushing can lead to the prevention of tooth decay. This study aimed to check the anti-cariogenic activity against Streptococcus mutants and Lactobacillus. acidophilus of six commercially available toothpastes using the Agar well diffusion method. Methods: The antimicrobial efficacy of different dentifrices was determined using the modified agar well diffusion method. Each dentifrice was separately plated in triplicates and the experiment was repeated thrice. Agar plates were inoculated with 20uL of 24h broth cultures of each bacterial isolate, 0.2mL of the respective dentifrice was introduced into each of the three wells and distilled water was introduced into the last well as control. The plates were incubated at 37 o C for 48 hours. Statistical analysis was done using the statistical package, SPSS, by applying one-way ANOVA and post-hoc Tuckey test. Results: All the experimental toothpaste groups being tested in this study presented antimicrobial activity against both bacterial pathogens, however, each differed in its efficacy. Comparison between different groups displayed significant results (p-value < 0.001). Among all the groups, Doctor's toothpaste showed the highest antimicrobial activity (Mean + SD) (34.16 +1.47) against S. mutans whereas the Paradontax showed the minimalist antimicrobial activity (12.3 + 5.2). Conclusion: Doctors' toothpaste showed the best anti-bacterial effect against both bacteria, while Paradontax showed the least activity.